2021
DOI: 10.1021/acsanm.1c00466
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscience-Led Antimicrobial Surface Engineering to Prevent Infections

Abstract: One of the major complications associated with the implantation of biomedical devices regardless of their function is biomaterial associated infection. Infections are generally initiated by opportunistic bacterial colonization and biofilm development on the surface of implanted biomaterials, rendering the infection impervious to host defenses and antimicrobials. Moreover, the infection around soft tissues also has a significant role in biomaterial-associated infections. It is well documented that the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 181 publications
0
10
0
Order By: Relevance
“…To promote the transition from lab research to practical applications, the overall performance of the bioinspired antibacterial surfaces should be improved enough to cope with complex, transient scenarios in the real world [ 76 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ]. First, a bioinspired antibacterial surface should be highly adaptive to a wide spectrum of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…To promote the transition from lab research to practical applications, the overall performance of the bioinspired antibacterial surfaces should be improved enough to cope with complex, transient scenarios in the real world [ 76 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ]. First, a bioinspired antibacterial surface should be highly adaptive to a wide spectrum of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Equation (2), when the diameter of the orifice is reduced, the diameter of the drop generated is also reduced [24]. Another equation derived for calculating the diameter of the drop generated from a liquid film where both gravity and flow rate of the liquid comes in play is D = 3.3{σ/ρ L g} 0.5 (3) It is observed that Equation ( 3) is suitable when the flow rate of the liquid is low, which gives a larger drop size but this is unprofessional for experimental applications as we prefer fine droplets, where the effect of gravitational force will be negligible for the drops ranging in size from 1-300 µm [24]. When the diameter of the orifice is minimized to 1 µm, the diameter of the drop speculated will be one tenth as sizable [1].…”
Section: Mathematical Formulationsmentioning
confidence: 99%
“…[10][11][12] Besides, (3) bacterial growth can be inhibited by antimicrobialleaching layers, which load antibiotics, antiseptics, and metal ions. [13][14][15] Although all the above strategies are effective under appropriate conditions, residual and drug-resistant bacteria remain intractable problems. 16 Antimicrobial peptide mimetics (AMPMs) are considered as a potential choice to solve the problem of bacterial drugresistance.…”
Section: Introductionmentioning
confidence: 99%